Halal Tourism in Thailand: Unraveling Muslim Tourists Perspectives on Culinary Practices and Requirements - Athifah Mufidah; Taufik Abdullah; Rijal Khaeran (Jurnal Pendidikan Ilmu Sosial, 2024)
Thailand experienced a remarkable surge in tourism, welcoming 19 million visitors in the first nine months of 2023—an impressive 271% increase from the previous year. Notably, 3.2 million of these tourists were Muslim, present an opportunity for Thailand to bolster its appeal by fostering a Muslim-friendly tourism environment, encompassing halal amenities. A key focus is on halal restaurants, as research indicates that Muslim tourists prioritize certified halal cuisines, playing a pivotal role in destination selection. This study diverges from culinary-centric approaches, employing the theory of social practices to explore the evolving awareness of dietary preferences among Muslim tourists in Thailand's major cities. By examining religious beliefs and lifestyle factors, the research seeks to document and analyze the perspectives of Muslim tourists on halal restaurants, shedding light on the interplay between food preferences, religious considerations, and tourism dynamics.